2022
DOI: 10.3390/biom12020198
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Gibberellin Treatment Enhances Melatonin Synthesis for Melatonin-Enriched Rice Production

Abstract: Melatonin production is induced by many abiotic and biotic stressors; it modulates the levels of many plant hormones and their signaling pathways. This study investigated the effects of plant hormones on melatonin synthesis. Melatonin synthesis in rice seedlings was significantly induced upon exogenous gibberellin 3 (GA3) treatment, while it was severely decreased by GA synthesis inhibitor paclobutrazol. In contrast, abscisic acid (ABA) strongly inhibited melatonin synthesis, whereas its inhibitor norflurazon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…As already seen, GA weighs in on a plethora of plant developmental processes. This knowledge could be used to promote its action, producing enriched functional foods [ 267 ]. By contrast, the inhibition of GA could be used to avoid GA-related proteins which can cause medical conditions such as allergic diseases to pepper, cedar [ 268 ], or strawberry [ 269 ].…”
Section: Current and Potential Applicationsmentioning
confidence: 99%
“…As already seen, GA weighs in on a plethora of plant developmental processes. This knowledge could be used to promote its action, producing enriched functional foods [ 267 ]. By contrast, the inhibition of GA could be used to avoid GA-related proteins which can cause medical conditions such as allergic diseases to pepper, cedar [ 268 ], or strawberry [ 269 ].…”
Section: Current and Potential Applicationsmentioning
confidence: 99%
“…73,74 For instance, the treatment of immature rice seeds with exogenous GAs resulted in higher endogenous MEL contents in rice seeds. 73 Likewise, BR treatment also induced several MEL genes and transgenic rice plants with downregulated BR biosynthesisrelated genes, such as DWARF4, DWARF11, and RAV-Like1 showed decreased MEL synthesis, indicating that BRs act as endogenous elicitors of MEL synthesis. 74 Additionally, the suppression of the serotonin Nacetyltransferase-2 (SNAT2) gene encoding the penultimate enzyme in MEL biosynthesis led to simultaneous decrease in both MEL and BR levels, 75 thus suggesting the varied levels of different phytohormones may regulate endogenous MEL contents in germinating seeds.…”
Section: Endogenous Mel Contents In Seedsmentioning
confidence: 99%
“…Though MEL also regulates endogenous levels of different phytohormones in plants, 27,72 phytohormones such as GAs or brassinosteroids (BRs) also act as endogenous elicitors to induce MEL synthesis and regulate endogenous MEL contents in seeds and seedlings 73,74 . For instance, the treatment of immature rice seeds with exogenous GAs resulted in higher endogenous MEL contents in rice seeds 73 . Likewise, BR treatment also induced several MEL genes and transgenic rice plants with downregulated BR biosynthesis‐related genes, such as DWARF4, DWARF11, and RAV‐Like1 showed decreased MEL synthesis, indicating that BRs act as endogenous elicitors of MEL synthesis 74 .…”
Section: Endogenous Mel Contents In Seedsmentioning
confidence: 99%
“…306 GA coupled with decreased expression of M2H and ASDAC improving rice seed quality with enriched melatonin levels. 313 Under stress condition, melatonin or its metabolites directly or indirectly scavenged ROS and RNS to maintain cellular ROS/RNS balance and then activate stress defense response, which demonstrated that scavenging excessive RNS is a potential mechanism for M2H or M3H in regulating plant life. AsA-GSH, as the important antioxidant system, could be involved in the M2H and M3H mediated stress response.…”
Section: Regulatory Mechanism Of Melatonin Metabolic Genes In Plant B...mentioning
confidence: 99%
“…The expression level of M3H had a significant effect on Arabidopsis flowering by decreasing the expression of GA biosynthetic genes ( KS , GA3ox1 , and GA3ox2 ), GA responsive factors ( MYB33 ), and flower inducer ( FT ) 306 . GA coupled with decreased expression of M2H and ASDAC improving rice seed quality with enriched melatonin levels 313 . Under stress condition, melatonin or its metabolites directly or indirectly scavenged ROS and RNS to maintain cellular ROS/RNS balance and then activate stress defense response, which demonstrated that scavenging excessive RNS is a potential mechanism for M2H or M3H in regulating plant life.…”
Section: The Metabolism Of Melatoninmentioning
confidence: 99%